El estado de flujo de efectivo y su incidencia en la toma de decisiones financieras de la empresa luderson s.a. ubicada en guayaquil, período 2022. - Santillán Quijano, Flavio Elian (2023)
The research project structures the cash flow statement and its impact on the financial decision making of the company Luderson S.A., located in Guayaquil, period 2022. located in Guayaquil, period 2022, this is dedicated to the cultivation of bananas and plantains and wholesale of fruits, which is its main source of economic income, however, presents an excess liquidity in the fiscal year mentioned above, which generates a problem of opportunity cost that may affect profitability over time, Therefore, the objective of the study was to determine the incidence of the cash flow statement in the financial decision making of the company, because this tool provides important information about the financial situation of the entity, with the purpose of making decisions that contribute to the improvement of the business activity, in this way it was possible to verify relevant data through the instruments, methods and research techniques used.